2022
DOI: 10.12775/jehs.2022.12.09.111
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism in relationships between of plasma creatinine and some neuro-endocrine parameters

Abstract: Background. Earlier we found that plasma uric acid and urea causes modulating effects on neuro-endocrine parameters, as well as reactive anxiety, but these effects are significantly different in men and women of different ages. The purpose of this study is to analyze the relationships between the plasma creatinine level and some psycho-neuro-endocrine parameters in the same cohort. Materials and Methods. The object of observation were almost healthy volunteers: 31 males (24÷69 y) and 30 females, from among the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Earlier we found that effects of plasma nitrogenous metabolites as urea, creatinine, and bilirubin on neuroendocrine parameters, as well as anxiety, are significantly different in men and women of different ages [7][8][9][10][11][12]. The purpose of this study is to analyze the relationships between the plasma uric acid level and some psychoneuro-endocrine parameters in the same cohort.…”
Section: Introductionmentioning
confidence: 96%
“…Earlier we found that effects of plasma nitrogenous metabolites as urea, creatinine, and bilirubin on neuroendocrine parameters, as well as anxiety, are significantly different in men and women of different ages [7][8][9][10][11][12]. The purpose of this study is to analyze the relationships between the plasma uric acid level and some psychoneuro-endocrine parameters in the same cohort.…”
Section: Introductionmentioning
confidence: 96%
“…During the realization of the project "Physiological activity of uric acid", our group new data were obtained in favor of this assumption. In particular, the level of uric acid in the serum through the corresponding nuclei of the cortex, amygdala, brainstem and medulla upregulate sympathetic tone and downregulate vagal tone [3,4,5], that is, it acts similarly to caffeine. However, the fact we obtained about a weak, but still positive (r=0,22) relationship between changes in uricemia (the level of which is comparable to the concentrations of adenosine and theophylline in in vitro immune tests) and relative content of CD8 + T cells in the blood, that is, theophyllinesensitive, at first glance, contradicts the classical position.…”
Section: Introductionmentioning
confidence: 99%
“…During the implementation of the project "Physiological activity of uric acid" [13,44], our group discovered four variants of the combination of levels of uricemia and uricosuria in patients with chronic pyelonephritis in the remission phase, which are accompanied by characteristic constellations of parameters of the central [7] and autonomic [5] nervous, endocrine [5], and immune [18,19,54] systems, as well as the exchange of nitrogenous metabolites and electrolytes [13], the levels of which correlate with uricemia and/or uricosuria. Similar tests, with the exception of EEG, were conducted in an experiment on healthy rats [3,4,[14][15][16][17]43].…”
Section: Introductionmentioning
confidence: 99%